Resolution of Antam Gold Selling and Buying Disputes Reviewed From Economic Analysis of Law Theory - Sri Wahyuni (Journal of Social Research, 2023)
There was an agreement to buy and sell Antam gold between the seller, namely PT Aneka Tambang Tbk, which is a State-Owned Enterprise, and the buyer, namely someone from Surabaya. This agreement has legal consequences for the parties who make it and must be implemented in good faith. As agreed, the buyer has the right to receive Antam gold and is obliged to pay a certain amount of money according to the agreement between the parties. On the other hand, the seller has the right to receive a certain amount of money and is obliged to provide Antam gold by the sale and purchase agreement agreed upon by the parties. In this case, the buyer has paid the amount of money according to the agreed nominal value, but not all of the Antam gold received has been received. The buyer has tried to ask the seller for their rights but they have not been given them. On the other hand, the seller is a State-Owned Enterprise which in essence must not cause state losses. Regarding the resolution of the case, it was carried out through the courts. The question arises of how to resolve the Antam gold buying and selling dispute in terms of economic analysis of law theory. The research method in this research uses a normative legal research method with a case approach. This research uses the theory of Economic Analysis of Law. The results of this research are to find out the resolution of Antam's gold buying and selling dispute through the court, considering the theory of economic analysis of law.